Kemampuan Menyimak Bahasa Jerman Melalui Media Deutschtrainer A1 - Magvira Magvira; Ambo Dalle (Phonologie : Journal of Language and Literature, 2023)
Abstract. This research is a classroom action research that aims to improve the German listening skills of class X IPS 2 SMAN 4 Luwu through Deutschtrainer A1 learning media.  The research was conducted in two cycles.  Each cycle contains the stages of planning, implementing, observing and reflecting.  The research data consisted of two types of data, namely qualitative data which is a description of the results of the implementation and results of observations during the learning process and quantitative data in the form of test results of students' listening abilities.  The average score for the listening ability of class X IPS 2 students in cycle I was 56.47 and increased in cycle II to 80.88.  The results showed that the Deutschtrainer A1 media could improve the German listening skills of class X IPS 2 students of SMAN 4 Luwu.Keyword: Listening Ability, Deutschtrainer A1, Germany